Analysis of heavy metal content (Pb, Cu, Mn, and Zn) in water and sediment of seagrass beds in Tihi-Tihi waters, Bontang City, East Kalimantan, Indonesia - Tandilese, Elma Dannari; Hamdhani, Hamdhani; Jailani, Jailani (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
Seagrass has clear economic benefits in supporting the availability of various commercial fish species and also serves multiple ecological functions. The presence of seagrass in marine waters can act as a bioindicator of heavy metal pollution, as it can absorb and accumulate contaminants. Until now, the exact concentration of heavy metals in the water and sediment of seagrass beds in Tihi-Tihi Village, Bontang City, has not been clearly known. This study aims to determine the content of heavy metals (Pb, Cu, Mn, and Zn) in the water and sediment of seagrass beds in Tihi-Tihi Village, Bontang City, East Kalimantan. The results showed that the concentrations of heavy metals (Pb, Cu, Mn, and Zn) in the water were the same across all stations, ranging between <0.001–<0.003 mg/L, which is below the quality standards set by the government. Lead (Pb) is the heavy metal of most concern due to its concentration falling within the Severe Effect Level. Further studies are needed to investigate the potential impacts of the high concentration of Pb in the sediment of this seagrass bed.